Organic Fertilizers From Basic Concepts to Applied Outcomes - Larramendy, Marcelo L.; Soloneski, Sonia (IntechOpen, 2016)
This book, Organic Fertilizers - From Basic Concepts to Applied Outcomes, is intended to provide an overview of emerging researchable issues related to the use of organic fertilizers that highlight recent research activities in applied organic fertilizers toward a sustainable agriculture and environment. We aimed to compile information from a diversity of sources into a single volume to give some real examples extending the concepts in organic fertilizers that may stimulate new research ideas and trends in the relevant fields.